The role and importance of foreign investments in ensuring economic growth - Khujakulova Nigora Rustamovna; Kodirova Mokhinur Bakhodir kizi (THE INNOVATION ECONOMY, 2026)
This article discusses the basic principles of effective use of investments, the role of investments in ensur ing economic growth and their successful management. The article presents and analyzes the views on the priority areas of attracting foreign investments, primarily foreign direct investments, in order to increase the competitiveness of the economy based on its modernization and diversification.